Evaluation of the electrical energy potential of woody biomass in the near region of the hydropower plant Tucuruí –Brazil - Brasil, A. C. M. (2020)
This paper determines the potential of installing power plants fired with wood residues generated at the sawmills located in the region of a 8 GW hydropower complex in the Amazon. Two different scenarios were considered: i) the residues are converted locally at the mills or ii) transported to a centralized power plant. To evaluate the existing electricity potential, sawmills were contacted and the amount and type of generated residues assessed. The LHV (lower heating value) of wood of native species processed at the mills was experimentally determined. Data from real biomass power plants was fitted to calculate efficiencies versus power. With LHV data and conversion efficiency, the potential of installing micro to large-scale biomass-fired power plants was estimated. In 2004 and 2014, sawmills around the Tucuruí dam generated 404×103 t of wood residues, showing that in the region there is a large untapped potential for energy valorization. If the residues were converted at the mills, 57 GWhe could be produced. The energy production would be around 2 times higher in the centralized scenario. The importance of the efficiency in determining biomass potentials or optimizing biomass supply chains is quantified. Ignoring the dependency of efficiency with power leads to erroneous conclusions.